2023
DOI: 10.3390/children10071215
|View full text |Cite
|
Sign up to set email alerts
|

Restoration Integrity in Primary Teeth Prepared Using Erbium/Yttrium–Aluminum–Garnet Laser: A Randomized Split-Mouth Clinical Study

Raghdah Abdrabuh,
Omar El Meligy,
Najat Farsi
et al.

Abstract: The most frequently used and universally accepted technique for removing caries is mechanical ablation of decayed tissues by rotating drills. New minimally invasive strategies, such as the use of lasers to perform highly controlled tissue ablation, have been introduced in dental practice. The aim of this study was to assess and compare treatment with a 2940 nm erbium/yttrium–aluminum–garnet (Er:YAG) laser versus a conventional rotary treatment during cavity preparation in children with regard to restoration in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…The clinical significance of the present study lies in the fact that the clinical success of the restorations used in this study was investigated and reported in a previous study, using precise clinical and radiographic evaluation standards, which resulted in outstandingly successful restorations [5]. The current research revealed instances of bond interface failures in both conventional and Er:YAG laser-prepared cavity preparations, underscoring the challenge of precisely assessing the bonding interface, which was a part of the success of the restoration, particularly the dentin floor interface, in a clinical setting using clinical assessment tools.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…The clinical significance of the present study lies in the fact that the clinical success of the restorations used in this study was investigated and reported in a previous study, using precise clinical and radiographic evaluation standards, which resulted in outstandingly successful restorations [5]. The current research revealed instances of bond interface failures in both conventional and Er:YAG laser-prepared cavity preparations, underscoring the challenge of precisely assessing the bonding interface, which was a part of the success of the restoration, particularly the dentin floor interface, in a clinical setting using clinical assessment tools.…”
Section: Discussionmentioning
confidence: 87%
“…Previous research has indicated that the Er:YAG laser has promise for application in cavity preparation within the field of pediatric dentistry. This is attributed to the enhanced cooperation observed among young patients when undergoing dental cavity preparation using the Er:YAG laser [5][6][7]. The aforementioned benefit can be ascribed to the absence of vibration, noise, and forceful water jet commonly associated with traditional cavity preparation techniques.…”
Section: Introductionmentioning
confidence: 99%